Effects of Experiential Quality on Experiential Loyalty: Evidence from Starbucks Coffee Chains in Pampanga, Philippines - Lacap, Jean Paolo (Animo Repository, 2022)
The study examines the effect of experiential quality on experiential loyalty among customers in Starbucks coffee chains in Pampanga, Philippines. Five hundred ninety-five customers were purposively sampled as respondents. By way of causal-predictive design and partial least squares path modeling, the results showed that experiential quality significantly and positively predicts experiential satisfaction, perceived value, and experiential trust. Concomitantly, it was found that perceived value is a trifocal predictor of experiential satisfaction, experiential trust, and experiential loyalty. The impact of experiential trust on experiential loyalty garnered the highest path coefficient, indicating its strong impact compared to the effect of experiential satisfaction on experiential loyalty, as well as perceived value on experiential loyalty. The mediation analysis showed that experiential satisfaction and experiential trust are both mediators of the relationship between experiential quality and experiential loyalty. However, experiential satisfaction has a stronger mediating effect compared to experiential trust.